Sex differences in patterns of white matter neuroplasticity after balance training in young adults - Kirby, Eric D.; Andrushko, Justin W.; Boyd, Lara A.; Koschutnig, Karl; D’Arcy, Ryan C. N. (Frontiers in Human Neuroscience, 2024)
In past work we demonstrated different patterns of white matter (WM) plasticity in females versus males associated with learning a lab-based unilateral motor skill. However, this work was completed in neurologically intact older adults. The current manuscript sought to replicate and expand upon these WM findings in two ways: 1) we investigated biological sex differences in neurologically intact young adults, and 2) participants learned a dynamic full-body balance task. 24 participants (14 female, 10 male) participated in the balance training intervention, and 28 were matched controls (16 female, 12 male). Both females and males demonstrated skill acquisition, yet there were significant differences in measures of WM between females and males. These data support a growing body of evidence suggesting that females exhibit increased WM neuroplasticity changes relative to males despite comparable changes in motor behaviour (e.g. balance). The biological sex differences reported here may represent an important factor to consider in both basic research (e.g. collapsing across females and males) as well as future clinical studies of neuroplasticity associated with motor function (e.g. tailored rehabilitation approaches).